Desain Karakter Motion Graphic Biografi W.R. Soepratman untuk Anak Muda - Diarrahman, Faisal Amri; Widyasari, Widyasari; Romadhona, Mahimma (Fakultas Desain Universitas Komputer Indonesia, 2024)
In a study, it is stated that Generation Z prefers consuming audio-visual content. In this case, motion graphics can be used as a media to portray the biography of W.R. Soepartman. However, in the motion graphic video, there is still no character design of W.R. Soepratman. Therefore, there is a need for the design of the character of W.R. Soepratman as the main character in the motion graphic video. The character design becomes the visual identity of the character of W.R. Soepratman as well as other characters in the motion graphic video. Therefore, character design becomes an important aspect in the design process and serves as a visual identity to portray the characteristics of W.R. Soepratman. Therefore, research is conducted in an effort to generate design ideas for the character design and develop them into a design concept suitable with motion graphic. The character design in the motion graphic biography of W.R. Soepratman serves as a visual asset that functions as the visual identity of historical figures and characters present in the motion graphics. A simple and minimalist character design is obtained with the primary function of depicting the character. Simple and minimalist character shape form can facilitate the animation process in motion graphics.